If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1z + 5 = -21 Reorder the terms: 5 + 1z = -21 Solving 5 + 1z = -21 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 1z = -21 + -5 Combine like terms: 5 + -5 = 0 0 + 1z = -21 + -5 1z = -21 + -5 Combine like terms: -21 + -5 = -26 1z = -26 Divide each side by '1'. z = -26 Simplifying z = -26
| 3x/x-2-4=14-4x/x-2 | | 3y^2+2yz-z^2=0 | | m/3(m+1)=3 | | -9+3n+10y-8y-6n+15= | | 4x^2/25*25/x^2 | | 22b+10=98 | | 2.50a+2.00=14.50 | | 2.50+2.00=14.50 | | x+63=180 | | s=20+0.5t | | 45h+44=179 | | 1/f=1/a+1/b | | 10p/3=-4 | | 8.95r+1.50=26.05 | | 6(n+75)+9n=1725 | | 21(3n)+21n=84 | | 6(n+75)9n=1725 | | 2(n+85)+(3n)=1345 | | 3(p-3)=35 | | 2(n+85)-3n=1345 | | 3(n+6)+5n=170 | | 12(20b)+13b=1265 | | 7(m+3)-6m=3(m+3) | | -10-20(y-15)=-4y-(y-5) | | -30(y-15)=-4+y-(y-5) | | 8=9x | | 7(x-19)=7.3 | | (-99)x=8 | | -3(m-10)-2(m+4)=-2+6m-(m+16) | | 7(x+4)-2(x-1)=-4(x-3)+36 | | 4*1-2y=2 | | 8a+7=6a+2 |